Characterization of Montmorillonite–Biochar Composite and Its Application in the Removal of Atrazine in Aqueous Solution and Soil - Wang, Pingping; Stenrød, Marianne; Wang, Liang; Yuan, Shankui; Mao, Liangang; Zhu, Lizhen; Zhang, Lan; Zhang, Yanning; Jiang, Hongyun; Zheng, Yongquan; Liu, Xingang (Frontiers in Environmental Science, 2022)
Atrazine is a widely used triazine herbicide, which poses a serious threat to human health and aquatic ecosystem. A montmorillonite-biochar composite (MMT/BC) was prepared for atrazine remediation. Biochar samples were characterized by Scanning electron microscope (SEM), Transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectrometer (XPS). Structure and morphology analysis of raw biochar (BC) and MMT/BC showed that MMT particles have been successfully coated on the surface of biochar. Sorption experiments in aqueous solution indicated that the MMT/BC has higher removal capacity of atrazine compared to BC (about 3.2 times). The sorption of atrazine onto the MMT/BC was primarily controlled by both physisorption and chemisorption mechanisms. The amendment of MMT/BC increased the sorption capacity of soils and delayed the degradation of atrazine. Findings from this work indicate that the MMT/BC composite can effectively improve the sorption capacity of atrazine in aquatic environment and farmland soil, and reduce the environmental risk.